The Strategy of Mudir in Reducing Religious Intergroup Bias in Lhoksukon, Aceh, Indonesia - Dedy Surya; Sulaiman Ismail; Hamdani Hamdani (UIN Sultan Aji Muhammad Idris Samarinda, 2022)
Intergroup relations, especially between religiously affiliated groups, have always been a discussion that attracts the attention of scholars. However, research that highlights the efforts and processes of harmonisation between groups is still very limited to study, especially with regard to educational settings. By providing a different perspective on the discussion of most scholars, this article photographs the success of mudir (leader of Islamic educational institutions) in maintaining the existence of modern pesantren amid in-group favouritism biased traditional Islamic society in Lhoksukon, Aceh, Indonesia. By using a case-study approach, this study traced and collected data through in-depth interviews with several informants such as mudir, pesantren teachers, Imum Chik (religious leaders), and residents around Dayah Terpadu Al-Muslimun Lhoksukon, Aceh, Indonesia. The results of this study show that the conformity initiated by mudir, especially in symbols owned by the surrounding community, is able to reduce conflict between groups. In addition, mudir also involves figures with religious authority to be catalysts for harmony. The study also argues that intergroup biases in religious segmentation can be minimised by re-evaluating to find similarities in social identities between groups.